Synthesis of 3-alkylthio(sulfo)-1,2,4-triazoles, containing methoxyphenyl substituents at C5 atoms, their antipyretic activity, propensity to adsorption and acute toxicity - Samelyuk, Y. G.; Kaplaushenko, A. G.; Самелюк, Юрій Геннадійович; Каплаушенко, Андрій Григорович (My University, 2014)
To find new low-toxic, biologically active compounds, we have synthesized a series of alkylthio(sulfo)derivatives of 1,2,4-triazoles, which contain 2-, 3-, 4-methoxyphenyl or 3,4,5- trimethoxyphenyl substitutes at the C5 atom of 1,2,4- triazole nucleus. The structure of the obtained compounds has been confirmed by complex of modern physical and chemical methods of analysis. Acute toxicity and antipyretic effects has been investigated, the data of surface activity and propensity to adsorption have been set for the synthesized compounds. Based on these data, the correlations of results of the biological activity towards data of adsorption properties of new compounds have been conducted.
Keywords: 1,2,4-triazoles; physical and chemical properties; antipyretic activity; propensity to adsorption; toxicity